Effect Of Magnesium Perchlorate Content on the Mechanical, Thermal Stability, and Dielectric Properties of Plasticized PMMA/PVC-g-PMMA Electrolytes. (16th November 2020) - Dung, Nguyen Thi Kim; Linh, Nguyen Thi Dieu; Tham, Do Quang; Chinh, Nguyen Thuy; Tan, Man Minh; Mai, Tran Thi; Trang, Nguyen Thi Thu; Thanh, Do Minh; Tung, Nguyen Quang; Hoang, Thai
Abstract : In this study, new types of gel polymer blend electrolytes (GPBEs) were prepared with the synthesized PVC-g-PMMA graft copolymer, PMMA, plasticizers (propylene carbonate (PC), dioctyl phthalate (DOP)), and different loadings of Mg(ClO4 )2 via the solution casting method using tetrahydrofuran as solvent. Fourier transform infrared (FTIR) spectra of the electrolytes showed mutual molecular interactions between Mg(ClO4 )2 and organic moieties. The scanning electron microscopy images of the GPBEs showed their wrinkled surface morphology due to their low elastic modulus and high flexibility. Energy-dispersive X-ray (EDX) spectroscopy and mapping technique revealed the regular distributions of all atomic elements such as Cl, Mg, O, and C in the doped GPBEs. With increasing the Mg salt concentration, Young's modulus and tensile strength of the GPBEs strongly decreased. Interestingly, the elongation at break of the GPBEs was higher than that of neat (undoped) GPBE and achieved the highest value of 215% at the salt content of 20 wt.%. The AC conductivity and ionic conductivity, as well as dielectric permittivity of plasticized PMMA/PVC-g-PMMA/Mg(ClO4 )2 GPBE, s increased with frequency and Mg(ClO4 )2 doping content. Ionic conductivity of the doped GPBEs can be achieved from 5.51 × 10 − 5 to 4.42 × 10 − 4 (S.cm -1 ) using Mg(ClO4 )2 contents in the range from 10 to 40 wt.%. The doped GPBEs are thermally stable up to 100°C with very low weight losses. The GPBE doped with 20 wt.% of Mg(ClO4 )2 can be used as a new type of electrolyte for developing Mg batteries.